Breaking up sitting time after stroke (BUST-stroke). Issue 9 (December 2018) - English, Coralie; Janssen, Heidi; Crowfoot, Gary; Callister, Robin; Dunn, Ashlee; Mackie, Paul; Oldmeadow, Christopher; Ong, Lin K; Palazzi, Kerrin; Patterson, Amanda J; Spratt, Neil J; Walker, F Rohan; et al.
Objectives: People with stroke sit for long periods each day, which may compromise blood glucose control and increase risk of recurrent stroke. Studies in other populations have found regular activity breaks have a significant immediate (within-day) positive effect on glucose metabolism. We examined the effects of breaking up uninterrupted sitting with frequent, short bouts of light-intensity physical activity in people with stroke on post-prandial plasma glucose and insulin. Methods: Randomized within-participant crossover trial. We included people between 3 months and 10 years post-stroke, ambulant with minimal assistance and not taking diabetic medication other than metformin. The three experimental conditions (completed in random order) were: sitting for 8 h uninterrupted, sitting with 3 min bouts of light-intensity exercise while standing every 30 min, or sitting with 3 min of walking every 30 min. Meals were standardized and bloods were collected half- to one-hourly via an intravenous cannula. Results: A total of 19 participants (9 female, mean [SD] age 68.2 [10.2]) completed the trial. The majority ( n  = 12, 63%) had mild stroke symptoms (National Institutes of Stroke Scale score 0–13). There was no significant effect of experimental condition on glucose (mean [SD] positive incremental area [+iAUC] mmol·L·h-1 under the curve during sitting 42.3 [29.5], standing 47.4 [23.1], walking 44.6 [26.5], p  = 0.563) or insulin (mean + iAUC pmol·L·h-1 sitting 14, 161 [7, 560], standing 14, 043 [8, 312], walking 14, 008 [8, 269], p  = 0.987). Conclusion: Frequent, short bouts of light-intensity physical activity did not have a significant effect on post-prandial plasma glucose and insulin in this sample of people with stroke. Further studies are needed to identify strategies that improve inactivity-related glucose metabolism after stroke.